The role of toll-like receptor 9 (TLR9) in autoimmunity : an examination into the relationship between gut microbiota and TLR9 in Systemic Lupus Erythematosus (SLE) - Yasuga, Hiroko (2019)
SLE is a complex autoimmune disease characterized by the production of anti-nuclear autoantibodies in a breakdown of self-tolerance. TLR9 is a receptor which recognises microorganism-associated unmethylated DNA. It is located in the endocytic pathway in B cells, dendritic cells (DCs), plasmacytoid DCs, and murine macrophages. Data from our lab has shown that TLR9 deletion in lupus-prone B6.Sle1 mice causes severe disease, consistent with other model systems. TLR9 is also expressed on intestinal epithelial cells, where it may play an important role in the recognition of gut microbiota. Several studies have suggested that the development of several autoimmune diseases is influenced by gut microbiota. However, the role of the microbiota in the development of SLE has not yet been clarified. The aim of this investigation was to assess the impact of the microbiome in the development of autoimmunity in TLR9 deficient Sle1 mice (Sle1TLR9-/-) mice. To assess the impact of TLR9 deficiency in the absence of Sle1, we first analysed wild type B6 and B6.TLR9-/- mice. The strategies to evaluate the impact of the microbiome on immunological traits included housing mice in facilities with different levels of cleanliness and using antibiotic treatment to eliminate the gut microbiome. The mice were aged, and we assessed immunological traits in spleen and purified DNA from stool for 16S rRNA sequencing analysis. We then examined the effect of antibiotic treatment on mild and severe autoimmune traits, that are in Sle1 and Sle1TLR9-/- mice. We analysed immunological traits in the spleen, kidneys, Peyer’s patches, mesenteric lymph nodes, and performed stool DNA sequencing. In summary, we determined that gut microbiota has an impact on several immunological phenotypes. However, it does not impact autoimmune traits such as autoantibody production and kidney pathology in Sle1TLR9-/-. Furthermore, DNA sequencing analysis revealed that the Sle1 background influences gut microbiota, but this is dominated by the impact of different animal facilities and their mothers. Taken together, this research highlights the importance of gut microbiota in the disease, and how much environment effects on bacteria abundance.